Understanding community hate crimes as an incorrigible proposition: Local political attitudes, path dependence, and the ceremonious reporting of hate crime statistics - Mills, Jack M. (Criminology, 2024)
The Hate Crime Statistics Act (HCSA) of 1990 requires the federal government to publicly release official hate crime statistics annually; the HCSA does not, however, mandate that local agencies submit hate crime reports to the government in the first place. Although research has evaluated the reporting of hate crime statistics in a dichotomous fashion (compliance vs. noncompliance), the current study suggests that the consistent and invariable reporting of zero hate crimes in a particular jurisdiction over time is unlikely and thus better conceptualized as a third response strategy: ceremonious compliance. We examine this strategy as a potentially unique institutional behavior, structured by local political and historical contexts, including discursive differences in the identification of hate crime as an important social problem, and localized histories of racial oppression. This research then uses multilevel multinomial logistic regression models to estimate variation in the likelihood of differential compliance strategies (i.e., true compliance, ceremonious compliance, noncompliance), according to several political and historical factors, including Republican vote share, location in the Confederate South, and historical lynchings. Findings reveal that political and historical contexts are important predictors of agency responses to hate crime, with a particular tendency toward ceremonious compliance in Republican-leaning locales.